UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA SISTEM PENCERNAAN MANUSIA - -, Mubaizah; Hikamah, Siti Roudlotul; Hasbiyati, Haning (JURNAL BIOSHELL, 2013)
Learning is a key activity of the educational process. Researchers conducted observations in class VIII SMP Islam Al-Mursyidiyah Virgin and approximately 85% of the data obtained shows student scores ? 70. This study aimed to determine Increased Activity and Student Results in studying the digestive system in humans with type STAD cooperative learning model. Type of research is a classroom action research (CAR). The procedure used is the model cycle Based on these results, the percentage of student learning activities in the first cycle of 82% and a second cycle of 93%. While the results of daily tests of students in the first cycle obtained average value 77.36, while on the second cycle of 86.05. It is proved that the activity and student learning outcomes can be improved with the implementation of cooperative learning model type STAD. For a particular subject, type STAD Cooperative Learning Model is used to avoid boredom in learning activities.Keywords: Type STAD Cooperative Learning, Learning Activity, Learning Outcomes.